An evaluation of the effectiveness of 'The Buddy' System as a support for ETeMS programme / Zaini Mohd Nor - Mohd Nor, Zaini (2006)
This qualitative study is designed to explore the effectiveness of the Buddy Support System ( BSS ) programme in Kuala Terengganu, in the State of Terengganu. This study is an attempt to understand the consequence of mentoring between teachers who are proficient in English, and Mathematics and Science teachers who are less proficient in English, through the Buddy Support System Programme. The research is conducted in the Kuala Terengganu district involving Mathematics and Science teachers, and English teachers from all secondary schools in that district. The data for this study are gathered from a questionnaire answered by all respondents. A total of 60 % of the Mathematics and Science teachers perceived the Buddy Support System as effective. Over 54% of the English teachers indicated that the support system is effective. 32 % of the respondents said that the Buddy System is not effective due to lack of practice on the part of the buddies. The findings of the study thus indicated that the Mathematics and Science teachers as well as the English teachers were ready for the implementation of ETeMS, and the Buddy Support System is effective to some extend in helping the buddies to be proficient in English. School administrators therefore should make sure that The Buddy Support System works well in their schools and everybody involved play their role to make it a success.